Services de santé dans la langue officielle du patient : liens avec la proximité, la région et les facteurs sociodémographiques - Fernandes, Daphné (Regards sur la société canadienne, 2025)
À l’aide des données tirées de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 et de la Base de données ouverte sur les établissements de soins de santé, la présente étude examine l’incidence de la proximité des établissements de santé, et d’autres facteurs régionaux et sociodémographiques, sur l’accès à des soins dans la langue de choix de la population de langue officielle en situation minoritaire au Canada. Dans cet article, les soins en concordance linguistique se rapportent aux personnes qui reçoivent des services de santé dans la langue officielle de leur choix (français ou anglais). L’analyse porte sur les adultes de 18 ans et plus vivant dans différentes régions du Canada.

Health services in a patient’s own official language: Associations with proximity, region and sociodemographic factors - Fernandes, Daphné (Insights on Canadian Society, 2025)
Using data from the 2022 Survey on the Official Language Minority Population and the Open Database of Healthcare Facilities, this study examines how distance to health care facilities, alongside regional and sociodemographic factors, relates to access to language-concordant care for the official language minority population in Canada. In this article, language-concordant care refers to individuals receiving health care services in their preferred official language (English or French). The analysis focuses on adults aged 18 and older living across Canada.

Systematic Search and Evaluation of mobile Apps for Wound Care Available in French-Language in Canada - Gagnon, Julie; Chartrand, Julie; Probst, Sebastian; Maillet, Éric; Reynolds, Emily; Chaplain, Valérie; St-Jean, Heidi; East, Raphaelle; Lalonde, Michelle (Canadian Journal of Nursing Research, 2025)
Background Wounds are a significant national health concern, impacting individuals, healthcare systems, and the environment. Despite efforts by organizations to promote evidence-based practices, gaps persist between theory and nurse practice in wound care. Mobile apps show promises in enhancing wound care delivery, but their rapid evolution, including adaptations into different languages such as French, raises concerns about reliability and regulation. Evaluating these apps is crucial for ensuring patient safety and effective wound management. Purpose To review and assess mobile wound care apps available in French for healthcare providers in Canada. Methods A systematic search was conducted across the literature and the two main Canadian online app stores (App Store and Google Play). The included mobile apps underwent quality evaluation using the user version of the Mobile Application Rating Scale (uMARS). Results The initial search retrieved 1,550 apps, of which 260 were screened and 5 included. Included apps were from France and were available on both stores. These apps varied in features, including wound dressing directory ( n = 3), best practices reminders ( n = 2), photography management and digital wound tracking ( n = 1), and total body surface area calculator ( n = 1). Evaluation using uMARS indicated total averages range from 3.52/5 to 4.10/5. The results offer scant insight into the design and evaluation of the apps included. Conclusions The study highlights the need for development and validation of a French wound care app tailored to Canadian healthcare contexts and best practice recommendations, emphasizing collaboration among nurses and stakeholders in technology enhancement for the benefit of Canadians’ health.

Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. , Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

Validation culturelle d’un outil numérique francophone pour l’histoire médicale en soins de santé primaires - McGraw, Monica; Dionne Merlin, Marjolaine; Dion, Cynthia; Renaud, Julie; Légère, Danika; Poirier, Marie-Dominique (Minorités linguistiques et société / Linguistic Minorities and Society, 2025)
La technologie de santé numérique s’intègre dans les soins de santé améliorant l’engagement des patients dans les décisions partagées, favorisant ainsi leur prise en charge et la qualité des soins. FirstHx développe des outils innovants dans cette optique, mais leur mise en oeuvre est complexe pour la population francophone dans un contexte majoritairement anglophone. Cette étude vise à valider culturellement cet outil et à évaluer la satisfaction des utilisateurs. Une méthodologie mixte séquentielle explicative est employée en trois phases : un sondage quantitatif pour tester la clarté des questions, des entretiens semi-dirigés pour explorer la traduction culturelle et la convivialité, et une validation par des experts via la méthode Delphi. L’outil validé optimisera les pratiques cliniques, normalisera la saisie des données d’anamnèse et ouvrira de nouvelles perspectives de recherche. Cette validation offrira à la population francophone un accès équitable à des outils numériques innovants, renforçant leur engagement dans leurs soins. Digital health technology is being integrated into healthcare, improving patient engagement in shared decision-making, thereby promoting their care and the quality of care. FirstHx develops innovative tools with this goal in mind, but their implementation is complex for the Francophone population in a predominantly English-speaking context. This study aims to culturally validate this tool and assess user satisfaction. A sequential explanatory mixed-method approach is used in three phases: a quantitative survey to test question clarity, semi-structured interviews to explore cultural translation and user-friendliness, and validation by experts using the Delphi method. The validated tool will optimize clinical practices, standardize the collection of medical history data, and open new research opportunities. This validation will provide the Francophone population with equitable access to innovative digital tools, strengthening their engagement in their healthcare.

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.